THE IMPACT OF WORK STRESS ON CYBERLOAFING BEHAVIOUR IN TRAVEL COMPANY EMPLOYEE’S POST COVID-19 PANDEMIC WITH SELF-CONTROL AS MEDIATING ROLE - Yenita , Yenita; Rahmadi, Ashari (International Journal of Application on Economics and Business, 2023)
Work stress is a form of emotional fatigue experienced by employee. During Covid-19, many of travel employee’s experienced work stress due to problems caused by the pandemic. This problem can encourage an employee to perform counter-productive activities such as cyberloafing at work. In 2020-2021, travel company is the most affected industry during pandemic. Travel company employee’s experience stress due to the workload due to the pandemic. This work stress encourages them to carry out cyberloafing activity during work hours. This study is to analyze the impact of work stress on cyberloafing behaviour on travel company employee’s post Covid-19 pandemics through self-control as a mediating role. This study uses quantitative descriptive method by distributing questionnaires to 177 employees in a travel company on Jakarta. PLS-based Structure Equation Modeling (SEM) technique with 95% confidence level has been used for analysis and generating results. The result of this study is work stress and self-control have a positive and significant effect on cyberloafing behaviour. Self-control was found to have positive but not significant effect as a mediating role between work stress and cyberloafing behaviour.